Application of PEI-Modified Magnetic Nanoparticles as Gene Transfer Vector for the Genetic Modification of Animals - Jinhui Cui; Haixin Cui; Yan Wang; Changjiao Sun; Kui Li; Hongyan Ren; Wei Du (Advances in Materials Science and Engineering)
To evaluate the performance of the magnetic nanoparticles as gene transfer vector for breeding transgenic animals, we investigated a new approach to deliver green fluorescent protein (GFP) gene to porcine kidney 15 (PK-15) and porcine embryonic fibroblast (PEF) cells using PEI-modified magnetic nanoparticles as gene vector. The morphology of the nanoparticles and nanoparticle/DNA complexes was characterized using scanning electron microscopy. It was found that the surface of the particles becomes coarse and rough with increased average diameter, which implied the effective conjugating between nanoparticles with DNA. The zeta potential of nanoparticle/DNA complexes drops down from +29.4 mV to +23.1 mV comparing with pure nanoparticles. Agarose gel electrophoresis experiments show that DNA plasmids can be protected effectively against degradation of exonuclease and endonuclease. The efficiency of gene delivery was affected by the mass ratio of nanoparticle/DNA and the amount of nanoparticle/DNA complexes. We confirm that the most optimal mass ratio of nanoparticle/DNA is 1  :  1 by conducting a series of experiments. This work provides important experimental basis for the application of the magnetic nanoparticles on gene delivery to porcine somatic cells, which is significant for the achieving of breeding new transgenic cloned pigs by using somatic cell nuclear transfer technique.